Dinuclear Ruthenium(II) Complexes as Two‐Photon, Time‐Resolved Emission Microscopy Probes for Cellular DNA1. (23rd January 2014) - Baggaley, Elizabeth; Gill, Martin R.; Green, Nicola H.; Turton, David; Sazanovich, Igor V.; Botchway, Stanley W.; Smythe, Carl; Haycock, John W.; Weinstein, Julia A.; Thomas, Jim A.
Abstract The first transition‐metal complex‐based two‐photon absorbing luminescence lifetime probes for cellular DNA are presented. This allows cell imaging of DNA free from endogenous fluorophores and potentially facilitates deep tissue imaging. In this initial study, ruthenium(II) luminophores are used as phosphorescent lifetime imaging microscopy (PLIM) probes for nuclear DNA in both live and fixed cells. The DNA‐bound probes display characteristic emission lifetimes of more than 160 ns, while shorter‐lived cytoplasmic emission is also observed. These timescales are orders of magnitude longer than conventional FLIM, leading to previously unattainable levels of sensitivity, and autofluorescence‐free imaging.